2011
DOI: 10.1016/j.bcp.2011.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Research update: Alpha7 nicotinic acetylcholine receptor mechanisms in Alzheimer's disease

Abstract: Aberrant amyloid-β peptide (Aβ) accumulation along with altered expression and function of nicotinic acetylcholine receptors (nAChRs) stand prominently in the etiology of Alzheimer's disease (AD). Since the discovery that Aβ is bound to α7 nAChRs under many experimental settings, including post-mortem AD brain, much effort has been expended to understand the implications of this interaction in the disease milieu. This research update will review the current literature on the α7 nAChR-Aβ interaction in vitro an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
148
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(152 citation statements)
references
References 135 publications
(168 reference statements)
1
148
0
3
Order By: Relevance
“…Since nicotine has been shown to evoke glutamate release via the ␣7nAChR [11], these studies support A␤ 42 binding near the nicotinic site on ␣7nAChR to evoke glutamate release. Conflicting data exists in the literature regarding the ␣7nAChR-A␤ interaction with studies supporting both receptor activation and inhibition [33]. These differences may be related to the model system employed as well as the aggregation state and concentration of A␤ used.…”
Section: Discussionmentioning
confidence: 99%
“…Since nicotine has been shown to evoke glutamate release via the ␣7nAChR [11], these studies support A␤ 42 binding near the nicotinic site on ␣7nAChR to evoke glutamate release. Conflicting data exists in the literature regarding the ␣7nAChR-A␤ interaction with studies supporting both receptor activation and inhibition [33]. These differences may be related to the model system employed as well as the aggregation state and concentration of A␤ used.…”
Section: Discussionmentioning
confidence: 99%
“…PFC deficits are also a component of dementias such as AD, where there is early accumulation of β-amyloid and phosphorylated tau early in the disease, including tangles in layer III pyramidal cells (17). All of these disorders involve genetic alterations (24,(57)(58)(59)(60) or molecular interactions (25,61) of/with α7-nAChR signaling, including evidence of reduced receptor expression in PFC of patients with schizophrenia (22) or autism spectrum disorders (60). Genetic alterations of α7-nAChRs in schizophrenia are particularly well established (18).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have also shown that α7-nAChR expression depends on neuregulin, another molecule linked to schizophrenia (21), and that smoking in schizophrenia may be a form of self-medication, normalizing expression of α7-nAChRs (22). More recent studies have linked α7-nAChRs to autism (23), attention deficit hyperactivity disorder [ADHD (24)], and AD (25), suggesting that a variety of dlPFC disorders are linked to alterations in α7-nAChR signaling. α7-nAChR agonists are currently under development as potential therapeutic treatments for these disorders, based in part on animal studies showing that systemic administration of α7-nAChR agonists can rescue WM deficits induced by NMDAR blockade (26,27).…”
mentioning
confidence: 99%
“…Thought of as the "missing link" between the histopathological hallmarks of amyloid or phosphorylated tau and the clinical manifestation of AD, a7 nAChRs constitute an important area of research (reviewed in Bencherif and Lippiello, 2010;Parri et al, 2011).…”
Section: A Alzheimer's Diseasementioning
confidence: 99%